Pengaruh Corporate Governance Dan Profitabilitas Terhadap Audit Report Lag Pada Perusahaan Real Estate Dan Property - Debbi Chyntia Ovami; Reza Hanafi Lubis (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2018)
This study aims to examine and analyze the effects of corporate governance (measured through managerial ownership, institutional ownership, independent commissioners and audit committees) and profitability to audit report lag on real estate and property companies in Indonesia. This type of research is causal research. Population in this research is Real Estate and Property firms listed on Indonesia Stock Exchange in period 2012-2016 number 61 company. The sampling technique used is purposive sampling obtained the number of observations of 170 units of analysis. The results showed that institutional ownership and independent commissioners had a negative and significant impact on audit report lag while managerial ownership, audit committee and profitability had no significant effect. Simultaneously, corporate governance as measured by managerial ownership, institutional ownership, independent commissioners, audit committees and profitability has significant and significant impact on audit report lag on real estate and property companies in Indonesia